2002
DOI: 10.2165/00003495-200262040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Drotrecogin Alfa (Activated)

Abstract: Drotrecogin alfa (activated), recombinant human activated protein C, inhibits coagulation and inflammation and promotes fibrinolysis in patients with severe sepsis. 850 patients with severe sepsis treated with intravenous drotrecogin alfa (activated) 24 microg/kg/h for 96 hours had a significantly greater reduction in 28-day all-cause mortality (24.7%) than 840 placebo recipients (30.8%) in a randomised, double-blind, placebo-controlled study. The drug was associated with a 19.4% reduction in the relative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 49 publications
0
9
0
2
Order By: Relevance
“…Recombinant human activated protein C (APC) is known to inhibit coagulation and inflammation, and to promote fibrinolysis in patients with severe sepsis [13]. Binding of APC to the endothelial cell protein C receptor results in a number of actions, including increased activity of APC itself and inhibition of both NF-κB and apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant human activated protein C (APC) is known to inhibit coagulation and inflammation, and to promote fibrinolysis in patients with severe sepsis [13]. Binding of APC to the endothelial cell protein C receptor results in a number of actions, including increased activity of APC itself and inhibition of both NF-κB and apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…The median plasma concentration of exogenous administrated APC at steady state is 0.045 mg mL À1 [9]. A previous study revealed an APC-dependent reduction of CD62P on platelet surface exclusively after activation with recombinant tissue factor [10].…”
Section: Introductionmentioning
confidence: 92%
“…Currently available strategies for the management of sepsis patients include: timely patient identification and diagnosis [15]; rapid identification of causative organisms; appropriate, timely antimicrobial therapy [4,14,16,17]; improved ventilatory techniques (lowpressure ventilation) [18,19]; appropriate (goal-directed) hemodynamic support [20]; targeted pharmacological therapies (drotrecogin alfa [activated]) [16], glucocorticoid therapy [21]; glycemic control (intensive insulin therapy) [22,23]; appropriate nutrition [16]; effective supportive therapies [24] (prophylaxis against stress ulcers, administration of anticoagulants, dialysis [25,26]); and patient management by highly qualified clinicians and nursing staff [4,14,16,17,19]. These strategies have helped to reduce the incidence of infections, support failing organs and prevent complications [20].…”
Section: Achieving Mortality Reductions In Sepsismentioning
confidence: 99%